Respostas

2013-09-30T21:56:46-03:00
A) x² -4x -5 = 0
∆ = (-4)² - 4*1*(-5) = 16 + 20 = 36
x = (-(-4) ± √36)/(2*1) = (4 ± 6)/2
x’ = (4 + 6)/2 = 5
x” = (4 - 6)/2 = -1
S = {5,-1}    

b) - x² + x + 12 = 0
∆ = (-1)² - 4*(-1)*(12) = 1 + 48 = 49
x = (-(-1) ± √49)/(2*(-1)) = (1 ± 7)/(-2)
x’ = (1 + 7)/-2 = -4
x” = (1 - 7)/-2 = 3
S = {-4,3}    

c) - x² + 6x -5 = 0
∆ = (6)² - 4*(-1)*(-5) = 36 - 20 = 16
x = (-6 ± √16)/(2*(-1)) = (-6 ± 4)/(-2)
x’ = (-6 + 4)/(-2) = 1
x” = (-6 - 4)/(-2) = 5
S = {1,5}   

d) 7x² - 7 = 0
∆ = (0)² - 4*7*(-7) = 0 + 196 = 196
x = (0 ± √196)/(2*7) = (± 14)/14
x’ = 14/2 = 7
x” = (-14)/2 = -7
S = {7,-7}  


e) 7x² + 2 = 30
∆ = (0)² - 4*7*2 = 0 - 56 = -56
x = (0 ± √-56)/(2*7)
S = { }
Não é possível em U = R


f) 2x² - 90 = 8

∆ = (0)² - 4*2*(-90) = 0 + 720 = 720
x = (0 ± √720)/(2*2) = (± 12√5)/4
x’ = 12√5/4 = 3√5
x” = -12√5/4 = -3√5
S = {3√5, -3√5}

Espero ter ajudado. Abraços